Dampak Pendidikan Pesantren terhadap Moral Bermasyarakat Santri Pondok Pesantren Tashilul Huda Kauman, Wiradesa, Pekalongan - Wirani Atqia; Aminatuz Zuhriyah (EL-TARBAWI, 2021)
The ever increase of moral degradation cases has proven the inability ofIndonesian modern educational institutions to create students with goodcharacter. On the contrary, Islamic boarding school educational institutionsare one of the institutions that are expected to be able to change the morals ofthe community, especially students to socialize through programs,regulations, and habits of students in Islamic boarding schools. This studyaims to see the impact of the Taslihul Huda Islamic Boarding Schooleducation on the morals of the santri community through existing activities,programs, and regulations. The researcher used interviews and observationsto find data from the head and boarding school administrators, thecommunity, and the students who were there, then the researchers analysedand processed the data by triangulation. From the results of the study, it canbe said that the existing programs and regulations at the Taslihul HudaIslamic boarding school are effective in shaping the morals of the santri andthe community's ability to provide positive responses to students inengaging with the community.Keywords: Islamic Boarding School; Morality; Society; Students